Condylar morphology and position changes after miniscrew-assisted rapid palatal expansion in skeletal Class III malocclusion adult patients with mandibular deviation and unilateral posterior crossbite - Shuai Chen; Chunxi Zhang; Kaili Zhang; Xiaoming Tan; Xun Xi; Yi Zhao; Dongxu Liu (SpringerOpen, 2022)
Abstract Background To evaluate the morphological and positional changes of mandibular condyle after miniscrew-assisted rapid palatal expansion (MARPE) in skeletal Class III malocclusion adult patients with horizontal mandibular deviation (MD). Methods The sample consisted of 15 patients with MD (6 males and 9 females, mean age 21.58 ± 3.12 years). The CBCT scans were taken before and after MARPE immediately. The pre- and post-registered images of the cranial base and mandible were measured, respectively, by Mimics. Results After expansion, the distance between superior condylar point and the Frankfort horizontal plane on the deviated side and the non-deviated side increased by 0.96 ± 0.60 mm (P = 0.011) and 0.70 ± 0.65 mm (P = 0.046); coronal condylar angle of the deviated side increased by 0.39° ± 0.34 (P = 0.028) and 0.06° ± 0.49 (P = 0.917) on the non-deviated side. No statistically significant differences were found when comparing the condylar position on both sides before and after treatment. The degree of mandibular deviation decreased 0.43 mm (P = 0.270). Conclusions This study suggested that for skeletal Class III malocclusion adult patients with horizontal MD, the condyle on the deviated side rotated toward the non-deviated side in the coronal direction; the condylar remodeling occurred mainly on the deviated side after MARPE in the vertical direction.